Land Suitability and Fertility Capability Evaluation For Land Reform Area in Maha Sarakham, Province, Thailand - Boonme, Soontaree (2005)
Land suitability evaluation is one of the most effective methods for proper agricultural land use planning as it evaluates the suitability of land for a specific crop. Soil clusters were obtained using cluster analysis which groups soils according to similar characteristics. Fertility Capability Classification of Soil (FCC) groups soils according to the kind of limitations present for agronomic management of the physical and chemical properties. For any particular soil, the FCC is presented as a code such as Lek, a soil which is loamy for topsoil and subsoil (L) having high leaching potential and low nutrient capital reserves. The fertility constraints were high leaching potential (e), and low nutrient capital reserves (k). The interpretation of the code provides information that guides the user in choosing the right practices for the classified soil. By knowing soil clusters, FCC, and the land suitability, farmers can identify the fertility and the limitations of their land and the most suitable crop to cultivate. The study was conducted in Khok Phuk Kut and Pong Deang Forest, Maha Sarakham Province, Northeast Thailand, which are both located within a land reform area that was allocated by the Thai Government to landless farmers for agricultural purposes. The study area was 2,915.81 ha. The study entailed creation of FCC unit and land suitability maps using Global Positioning System (GPS) and Geographic Information System (GIs) as well as grouping soil series into soil clusters based on their physical and chemical properties (by cluster analysis). Conformity of land suitability and present land use was also considered. The base maps of administrative boundary, topography, climate, soil series, and present land use were collected. GIs was used to digitize the boundary of study area based on a map of the administrative boundaries of Maha Sarakham Province, Thailand. The boundary of the study area was overlaid with the soil series map using GIs. GPS was used to locate soil sampling points and features. The number of soil samples was based on the size of the area. Soil samples were analyzed based on important physical and chemical properties relevant to cluster analysis, FCC, and the Land Development Department's land quality of land use requirement for major economic crops. FCC is based on quantitative topsoil and subsoil parameters (termed soil type and substrata type) and condition modifiers, directly relevant to plant growth. Soil series were grouped into soil clusters by cluster analysis based on physical and chemical properties. Using cluster analysis, the soil series were grouped into three clusters as follows: (i) Ban Phai and Phra Thongkhom series (Bpi and Ptk), (ii) Ubon series (Ub) and (iii) Maha Sarakham and Non Deang series (Msk and Ndg). Based on the iii identification of FCC units, the soils of the study area for both topsoil and subsoil were loamy sand (S) or sandy loam (L). Their fertility constraints were high rate of infiltration, low water-holding capacity, low nutrient capital reserves (k), and Altoxicity (a). Land suitability classification of the study area for major economic crops such as rice (transplanted, direct seeded), upland rice, cassava and sugarcane was based on soil series. An area of 2,905.67 ha was found not suitable (N) for rice (transplanted, direct seeded) and upland rice. The same area was marginally suitable (S3) for cassava. It was marginally suitable for sugarcane (2,882.24 ha), and only 23.43 ha was not suitable. The fertility constraints were soil texture or structure. This study can contribute to the generation of information usehl in characterizing the soil into classes, group of soils, as well as evaluating the fertility of the land and also land suitability for the above-mentioned crops. The conformity of land suitability and present land use can ensure the proper use of land. The proper landuse planning management can be practiced in the land reform area.